Enhancement of oxygen reduction reaction activities by Pt nanoclusters decorated on ordered mesoporous porphyrinic carbons. Issue 16 (17th March 2016) - Hwang, Sun-Mi; Choi, YongMan; Kim, Min Gyu; Sohn, Young-Jun; Cheon, Jae Yeong; Joo, Sang Hoon; Yim, Sung-Dae; Kuttiyiel, Kurian A.; Sasaki, Kotaro; Adzic, Radoslav R.; Park, Gu-Gon
Abstract : The high cost of Pt-based membrane electrode assemblies (MEAs) is a critical hurdle for the commercialization of polymer electrolyte fuel cells (PEFCs). Abstract : The high cost of Pt-based membrane electrode assemblies (MEAs) is a critical hurdle for the commercialization of polymer electrolyte fuel cells (PEFCs). Recently, non-precious metal-based catalysts (NPMCs) have demonstrated much enhanced activity but their oxygen reduction reaction (ORR) activity is still inferior to that of Pt-based catalysts resulting in a much thicker electrode in the MEA. For the reduction of mass transport and ohmic overpotential we adopted a new concept of catalyst that combines an ultra-low amount of Pt nanoclusters with metal–nitrogen (M–N x ) doped ordered mesoporous porphyrinic carbon (FeCo–OMPC(L)). The 5 wt% Pt/FeCo–OMPC(L) showed a 2-fold enhancement in activities compared to a higher loading of Pt. Our experimental results supported by first-principles calculations indicate that a trace amount of Pt nanoclusters on FeCo–OMPC(L) significantly enhances the ORR activity due to their electronic effect as well as geometric effect from the reduced active sites. In terms of fuel cell commercialization, this class of catalysts is a promising candidate due to the limited use of Pt in the MEA.